IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DI UNIVERSITAS PAMULANG - Yenny Merinatul Hasanah (Jurnal Administrasi Pendidikan, 2023)
This research aims to find out the implementation of character education management at Universitas Pamulang and to find out the barrier factors in implementing character education. This research applied qualitative approach. The subjects of this research consisted of the foundation, rector, team of vice rector III, lecturers, and students of Universitas Pamulang. The data in this research were collected by observation, document analyses, and interviews. The technique of data analysis used referred to data analysis of interactive model, which is triangulation.The findings of the implementation of character education management were: First, the planning to grow shared awareness and to equalize the perception on the importance of value or character integration. Second, organizing the distributions of tasks, authorities, and responsibilities to the whole lecturers, especially the lecturers of religion subject and the team of Vice Rector III.Third, mobilizing the academic, non-academic activities; ways and processes to improve the activities. Fourth, controlling; observing what have been achieved and felt by the implementation of education character by the foundation, rector, all lecturers, team of Vice Rector III, religion subject lecturers, and students.Meanwhile there was a barrier in implementing the character education management at UniversitasPamulang. That was the limited human resources that actively implemented the existing programs.